Pengaruh Corporate Governance terhadap Tax Avoidance - Nur’aini, Dwi Sahla; Sherlita, Erly (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The practice of tax avoidance still occurs a lot in Indonesia, this causes a reduction in tax revenues which results in a decrease in state revenues. The application of good corporate governance is needed in companies to reduce tax avoidance actions. The purpose of this study is to empirically prove the influence of institutional ownership, independent commissioners, and audit committees on tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange between 2012 and 2021. The method used is a quantitative approach with the verification descriptive method. The study population consisted of 81 companies and purposive sampling was used to take samples in order to obtain 12 companies that fit the research criteria. By using Eviews 12, statistical calculations were performed using panel data regression analysis. The research findings show that partially the institutional ownership and independent commissioner variables have a negative effect on tax avoidance, while the audit committee variable has no effect on tax avoidance. In addition, the results of the study simultaneously show that institutional ownership, independent commissioners, and audit committee variables have an effect on tax avoidance.